Axial Modification of Cobalt Complexes on Heterogeneous Surface with Enhanced Electron Transfer for Carbon Dioxide Reduction. (18th August 2020) - Wang, Jiong; Huang, Xiang; Xi, Shibo; Xu, Hu; Wang, Xin
Abstract: Efficient electron communication between molecular catalyst and support is critical for heterogeneous molecular electrocatalysis and yet it is often overlooked during the catalyst design. Taking CO2 electro‐reduction on tetraphenylporphyrin cobalt (PCo) immobilized onto graphene as an example, we demonstrate that adding a relay molecule improves the interfacial electron communication. While the directly immobilized PCo on graphene exhibits relatively poor electron communications, it is found that diphenyl sulfide serves as an axial ligand for PCo and it improves the redox activity of PCo on the graphene surface to facilitate the generation of [PCo] . ‐ active sites for CO2 reduction. Thus, the turnover frequencies of the immobilized Co complexes are increased. Systematic structural analysis indicates that the benzene rings of diphenyl sulfide exhibit strong face‐to‐face stacking with graphene, which is proposed as an efficient medium to facilitate the interfacial electron communication. Abstract : Diphenyl sulfide can be used as an axial ligand for tetraphenylporphyrin cobalt. The axial coordination promotes the redox activity of tetraphenylporphyrin cobalt immobilized onto graphene surface through van der Waals interaction, and facilitates the generation of a reduced state of tetraphenylporphyrin cobalt to serve as the active site for electrochemical CO2 reduction.